2008
DOI: 10.1007/s11202-008-0102-0
|View full text |Cite
|
Sign up to set email alerts
|

Increasing smoothness of solutions to a hyperbolic system on the plane with delay in the boundary conditions

Abstract: Under consideration is a mixed problem in the half-strip Π = {(x, t) : 0 < x < 1, t > 0} for a first order homogeneous linear hyperbolic system with delay in t in the boundary conditions. We study the behavior of the Laplace transform of a solution to this problem for the large values of the complex parameter. The boundary conditions are found under which the smoothness of a solution to the corresponding mixed problem increases with t.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…n -norm of the function (4.21) can be estimated from above by 2d max 22) where K > 0 is a constant that depends on the coefficients a and b but does not depend on the function u l . Thus Claim 1 is proved.…”
Section: Smoothing Propertymentioning
confidence: 99%
See 1 more Smart Citation
“…n -norm of the function (4.21) can be estimated from above by 2d max 22) where K > 0 is a constant that depends on the coefficients a and b but does not depend on the function u l . Thus Claim 1 is proved.…”
Section: Smoothing Propertymentioning
confidence: 99%
“…It is also shown that the stabilization property is closely related to increasing smoothness of solutions to the perturbed autonomous problems. In the autonomous strictly hyperbolic case the smoothing effect is addressed in [10,21,22], while in the non-autonomous weakly hyperbolic case it is investigated in [16,17].…”
Section: Previous Workmentioning
confidence: 99%